Pengembangan nilai Islami peserta didik melalui integrasi Alquran dan Hadis dalam pembelajaran biologi - Mualimin, Mualimin (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2020)
National education aims to shape people of faith and piety and noble character, not only to develop the potential of cognitive intelligence. One effort that can be done to realize these goals is to develop Islamic values of students through the integration of the Qur'an and Hadith in learning biology. Through the integration of the Qur'an and Hadith in biology learning, students can gain knowledge about the concept of biology while at the same time developing Islamic values. Integration of the Qur'an and Hadith in learning biology can be done by: 1) Recording and analyzing verses of the Qur'an and Hadith that are in accordance with the subject or biological material both implicitly or explicitly, 2) Implementing the integration of verses of the Qur'an and Hadith found in the process of learning biology by selecting certain appropriate learning models; 3) Evaluating the integration process that has been done in the biology learning process. The integration of Al-Qur'an and Hadith in learning biology needs to be done to foster Islamic values in students to achieve national education goals.